Epidemiological Investigation of Salmonella bacteria in broiler carcasses marked in Hama markets (Journal of Hama University, 2019)
The search has been performed on 15 retail shops in local markets of Hama city. 100 samples of broiler carcasses were collected from retail shops during the presentation in markets. in order to determine if there is contamination of broiler chicken meat by Salmonella bacteria. Using specific mediums to isolate Salmonella bacteria, it was found that 11 samples of 100 a samples taken from retail shops during the presentation in markets were positive with overall prevalence (11%) It is indicative of risk for consumers of broiler meat that is contaminated with Salmonella bacteria and sold in shops in the local markets in Hama city. there contaminated meat consider as threat to public health because of these bacteria are transmissible through food, causing food poisoning in humans.